The Role of Sir Syed's Urdu Dictionary in the Evolution of Urdu Lexicography - Bibi Ameena (بازیافت, 2018)
Sir Syed Ahmed Khan was a well known Muslim scholar, reformist, educationist and writer of Persian, Arabic and Urdu languages. He is often described as two nation theory founder. He awakened the Muslims for the revival of their past position. His contribution is multi dimensional, ranging from practical efforts in the field of education and socio-political awareness to theoretical views in religion and literature. One of his contributions towards Urdu language was his lexicography. In 1868 Sir Syed Ahmed Khan started to compile an Urdu dictionary named Lughat-e-Zaban-e-Urdu and published its contents in Aligarh Institute Gazette but later he could not complete it. This write up deals with the critical evaluation of Sir Syed's Namoona-e-Lughat-e-Zaban-e-Urdu and also highlights its significance in the history of Urdu lexicography.